Liability of Maritime Carrier for the Transportation of Shipped Goods on Deck - Ahmed Khalil, Dr. Raed; Hashim Hamdoon, Dr. Rian (Basra studies journal, 2023)
The common way to transport goods by sea is to ship them in the places designated for them, i.e. in the wards of the ship, but the carrier often resorts to transporting goods on the deck of the ship, which exposes them to the dangers of the sea and weather fluctuations, which may lead to damage or complete damage to them. Therefore, the legislators in many countries, including the Iraqi legislator, have set special texts that dealt with the issue of transporting goods on deck. According to the enforceable Iraqi Transport Law No. 80 of 1983, the carrier’s non-responsibility for the loss or damage of the goods or the delay in their delivery in the event of shipped on the deck if the carrier agrees on that through the express agreement which is stated in the shipping document. This position is consistent with the provisions of the Hamburg Convention of 1978 in this regard. These provisions were appropriate to the conditions of maritime transport during their issuance, but the changes in this sector and the emergence of ships dedicated to transporting containers on the deck of the ship, which reduced the risks afflicting the goods to a large extent, made the consent of the shipper a matter of consideration. This matter calls us to investigate the feasibility of obtaining the consent of the shipper or not if the goods are transported on the deck of these specialized ships. It has become clear to us that there are shortcomings in the Iraqi legislation in dealing with transport on deck, which requires the approval of the shipper, regardless of the type of ship used in transport, and not keeping pace with developments in the container ship industry. Therefore, this study proposes to the Iraqi legislator to amend the legal texts regulating the transport of goods on deck, assuming the implied consent of the shipper in the event of transporting his goods in containers on the deck of the ship designated for this type of transport.